2021
DOI: 10.1007/s00294-021-01157-4
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of conidial fusion in the asexual fungus Verticillium dahliae as a useful system for the study of non-sexual genetic interactions

Abstract: Cell-to-cell fusion is a fundamental biological process across the tree of life. In filamentous fungi, somatic fusion (or anastomosis) is required for the normal development of their syncytial hyphal networks, and it can initiate non-sexual genetic exchange processes, such as horizontal genetic transfer and the parasexual cycle. Although these could be important drivers of the evolution of asexual fungi, this remains a largely unexplored possibility due to the lack of suitable resources for their study in thes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 67 publications
1
33
0
Order By: Relevance
“…We also used resistance cassette-specific primers for PCR screening of 14 of these heterokaryons, which confirmed their heterokaryotic nature. Given the complete suppression of conidial fusion on PDA and the previously demonstrated possibility of conidial fusion in a xylem sap-simulating medium [ 37 ], our results suggest that the isolated “compatible” and “incompatible” heterokaryons arose from fusion between strains in planta .
Fig.
…”
Section: Resultsmentioning
confidence: 56%
See 3 more Smart Citations
“…We also used resistance cassette-specific primers for PCR screening of 14 of these heterokaryons, which confirmed their heterokaryotic nature. Given the complete suppression of conidial fusion on PDA and the previously demonstrated possibility of conidial fusion in a xylem sap-simulating medium [ 37 ], our results suggest that the isolated “compatible” and “incompatible” heterokaryons arose from fusion between strains in planta .
Fig.
…”
Section: Resultsmentioning
confidence: 56%
“…Starvation induces significantly CAT-mediated fusion of V. dahliae conidia/germlings [ 37 ], and this motivated us to investigate the possibility of conidial fusion between strains of different VCGs under such conditions. Seven representative strains (Additional file 1 : Table S1 [ 36 38 ]; Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Reactive oxygen species (ROS) are known to play an important role in redox signaling pathways, including cell differentiation, development, and cytoskeleton remodeling [ 48 ]. NADPH-oxidases (NOX) are responsible for the production of superoxide (ROS) by oxidizing NADPH and reducing molecular oxygen, which is believed to be involved during communication, cell fusion, and CAT fusion in several fungi, e.g., N. crassa, F. oxysporum, and V. dahliae [ 48 , 49 , 50 , 51 ]. It has been shown that NADPH oxidase BcNoxA or Nox regulator BcNoxR gene deletion mutant of Grey mold Botrytis cinerea were defective in CAT fusion [ 52 ].…”
Section: Discussionmentioning
confidence: 99%